The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21207660
|View full text |Cite
|
Sign up to set email alerts
|

Copper Toxicity Links to Pathogenesis of Alzheimer’s Disease and Therapeutics Approaches

Abstract: Alzheimer’s disease (AD) is an irreversible, age-related progressive neurological disorder, and the most common type of dementia in aged people. Neuropathological lesions of AD are neurofibrillary tangles (NFTs), and senile plaques comprise the accumulated amyloid-beta (Aβ), loaded with metal ions including Cu, Fe, or Zn. Some reports have identified metal dyshomeostasis as a neurotoxic factor of AD, among which Cu ions seem to be a central cationic metal in the formation of plaque and soluble oligomers, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 336 publications
(416 reference statements)
4
79
0
2
Order By: Relevance
“…38 Interestingly, Parkinson's and Alzheimer's diseases have been associated with both high and low copper levels in the brain. 39,40 Corroborating our studies, increased histone acetylation was associated with reduced HDAC levels in mouse brains as well as midbrain tissues of patients with Parkinson's disease. 41 Previous studies have shown a role for class IIa HDACs in gene expression regulation of cardiac hypertrophy and contractile dysfunction.…”
Section: Q29supporting
confidence: 74%
“…38 Interestingly, Parkinson's and Alzheimer's diseases have been associated with both high and low copper levels in the brain. 39,40 Corroborating our studies, increased histone acetylation was associated with reduced HDAC levels in mouse brains as well as midbrain tissues of patients with Parkinson's disease. 41 Previous studies have shown a role for class IIa HDACs in gene expression regulation of cardiac hypertrophy and contractile dysfunction.…”
Section: Q29supporting
confidence: 74%
“…Some studies reported the potential role of Aβ monomers as antioxidants, depending on the metal ion concentration in vitro [ 49 , 50 ]. In contrast, other studies showed that oligomeric Aβ, the dominant form in patients with AD, promotes ROS production in cooperation with metal ions in vitro and in vivo [ 51 , 52 , 53 , 54 ]. In addition, inhibition of the γ-secretase activity was reported to reduce the levels of ROS and oxidize proteins, and to enhance resistance to oxidative stress [ 55 ].…”
Section: Dysregulation Of Redox Homeostasis In Neurodegenerative Diseasesmentioning
confidence: 97%
“…Major pathological hallmarks of AD are senile plaques (SPs), composed of self-polymerized amyloid-β peptide (Aβ), and neurofibrillary tangles (NFTs) of hyperphosphorylated tau proteins (Selkoe, 1991;Hardy and Higgins, 1992). In accordance with the metal hypothesis of AD, Aβ deposition, and tau hyperphosphorylation are aggravated by metal ions, thus promoting the development of AD (Liu et al, 2011;Zhang et al, 2019;Ejaz et al, 2020;Singh et al, 2020;Spotorno et al, 2020). The "metal hypothesis" describes the unbalanced theory of the level and location of metal ions in the pathogenesis of AD (Yang et al, 2019;Patel and Aschner, 2021).…”
Section: Introductionmentioning
confidence: 99%